Predictors of Preterm Birth among Mothers Who Gave Birth in Silte Zone Public Hospitals, Southern Ethiopia - Jida Ali Hassen; Mengistu Nunemo Handiso; Bitiya Wossen Admassu (Hindawi Limited, 2021)
Background. A preterm birth is the leading cause of death in both neonatal and children under five years of age every year throughout the world, particularly in Sub-Saharan Africa. The causes of a preterm birth are complex and multifactorial; many risk factors that contribute it are not fully understood. The aim of this study was to identify predictors of a preterm birth among mothers who gave birth in Silte Zone Public Hospitals, Southern Ethiopia (2019/20). Methods and Materials. A hospital-based unmatched case-control study design was carried out from July 15th to October 30th, 2019, by assigning mothers who gave preterm births as cases and those with term births as controls. A total of 365 respondents (91 cases and 274 controls) were selected by a consecutive simple random sampling until the required sample size was achieved. For each case, three consecutive controls were included. Data were collected using a structured interview questionnaire complement with record reviewing. The data were entered into Epi Info 7 and exported into SPSS 25 for analysis. Descriptive analysis was computed to obtain summary values for cases and controls separately. All candidate variables in bivariate analysis were entered into the multivariable logistic regression model by using the backward likelihood ratio selection methods. Finally, variables with p value ≤ 0.05 were considered as potential determinants of a preterm birth and reported in the form of adjusted odds ratio with 95% confidence interval. Results. Among a total of 365 mothers who gave live birth, 91 (24.9%) were cases compared to 274 (75.1%) which were controls. The final multivariable logistic regression analysis results showed that having history of a previous preterm birth (AOR=3.51; 95%CI=1.40−8.81), having shorter interpregnancy interval (AOR=4.46; 95%CI=1.95−10.21), experiencing obstetric complication (AOR=3.82; 95%CI=1.62−9.00), and having infant born with low birth weight (AOR=5.58; 95%CI=2.39−13.03) were found to be independent predictors of a preterm birth. Conclusions. According to this finding, mothers having previous history of a preterm birth, experiencing obstetric complication, having shorter interpregnancy interval, and having infant born with low birth weight were reported as the independent predictors of a preterm birth. Improving the quality of antepartum and intrapartum, counseling on birth space, creating awareness on family planning, and early screening of preterm determinants are mandatory.